A cutting force model for rotary ultrasonic machining of brittle materials - Liu, DeFu; Cong, W. L.; Pei, Zhijian J.; Tang, YongJun (My University, 2012)
Knowing cutting force in rotary ultrasonic machining(RUM)can help optimizing input variables.RUM of brittle materials has been investigated both experimentally and theoretically.However,there are no reports on cutting force models for RUM of brittle materials.This paper present same mechanistic model for cutting force in RUM of brittle materials. Assuming that brittle fracture is the primary mechanism of material removal in RUM of brittle materials,the cutting force model is developed step by step.On the basis of this mechanistic model,relationships between cutting force and in put variables(such as spindle speed,feed rate,ultrasonic vibration amplitude,abrasive size,and abrasive concentration)are predicted.Experiments are conducted for model verification and experimental results agree well with model predictions.
Keywords: Brittle material; Ceramic; Cutting force; Drilling; Predictive model; Rotary ultrasonic machining